2020
DOI: 10.1080/01919512.2020.1839739
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review and Research Needs of Ozone Applications Related to Virus Inactivation: Potential Implications for SARS-CoV-2

Abstract: Ozone disinfection has demonstrated high efficacy against enveloped and non-enveloped viruses, including viruses similar in morphology to SARS-CoV-2. Due to this efficacy, numerous gaseous and aqueous phase ozone applications have emerged to potentially inhibit virus persistence in aerosols, surfaces, and water. This review identifies the exposure requirements for virus inactivation and important safety considerations for applications within the built environment (i.e. occupied/unoccupied spaces, air/water/was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 123 publications
(116 reference statements)
0
26
0
1
Order By: Relevance
“…With regards to SARS-CoV-2, further research is needed about the disinfection with ozone to determine the efficacy of commercial devices and the minimum ozone CT values (residual concentrations and contact time) to meet the required log10 virus reduction. The current knowledge about the efficacy of ozone for the inactivation of other viruses suggests that ozone is likely to be highly effective at inactivating SARS-CoV-2 in water ( Morrison et al, 2021 ). This statement derives from many studies which demonstrated that ozone at low CT was effective at rapidly inactivating various types of viruses in wastewater or potable water with reductions of 4-log10 ( Morrison et al, 2021 ).…”
Section: Fate Of Covs and Sars-cov-2 Through The Stages Of The Wastewater Treatment Linementioning
confidence: 99%
See 1 more Smart Citation
“…With regards to SARS-CoV-2, further research is needed about the disinfection with ozone to determine the efficacy of commercial devices and the minimum ozone CT values (residual concentrations and contact time) to meet the required log10 virus reduction. The current knowledge about the efficacy of ozone for the inactivation of other viruses suggests that ozone is likely to be highly effective at inactivating SARS-CoV-2 in water ( Morrison et al, 2021 ). This statement derives from many studies which demonstrated that ozone at low CT was effective at rapidly inactivating various types of viruses in wastewater or potable water with reductions of 4-log10 ( Morrison et al, 2021 ).…”
Section: Fate Of Covs and Sars-cov-2 Through The Stages Of The Wastewater Treatment Linementioning
confidence: 99%
“…The current knowledge about the efficacy of ozone for the inactivation of other viruses suggests that ozone is likely to be highly effective at inactivating SARS-CoV-2 in water ( Morrison et al, 2021 ). This statement derives from many studies which demonstrated that ozone at low CT was effective at rapidly inactivating various types of viruses in wastewater or potable water with reductions of 4-log10 ( Morrison et al, 2021 ).…”
Section: Fate Of Covs and Sars-cov-2 Through The Stages Of The Wastewater Treatment Linementioning
confidence: 99%
“…Therefore, the ozonized water has been shown to inactivate numerous RNA and DNA viruses, including SARS-CoV-2 [ 20 , 21 ]. Due to shortages of PPE at the beginning of the COVID-19 pandemic, gaseous ozone disinfection becomes an attractive tool, providing further use of disposable protective equipment [ 8 , 22 , 23 ]. Moreover, the low cost of ozone generators makes them easily accessible; therefore, they began to be widely applied to decontaminate many closed spaces, such as offices, classrooms, churches, hospitals, and public utility buildings.…”
Section: Introductionmentioning
confidence: 99%
“…The first uses of ozone was the drinking water disinfection with early full-scale treatment plants since the beginning of XX century [13] . Although there is a vast literature on the ozone concentration and exposure times needed for bacterial and protozoan inactivation in wastewater treatment, scarce data are available for controlling viral contamination [14] . Previous data showed that both murine coronavirus and SARS-CoV-1 [15] , [16] are readily inactivated by O 3 treatment especially when combined with high relative humidity (RH) and this outcome has been conveyed to SARS-CoV-2 based on a recent computational analysis [17] .…”
Section: Introductionmentioning
confidence: 99%
“…temperature and humidity, the ozone concentration and contact times, for a broad number of independent viruses [18] . The ozone could be an efficient potential disinfectant against the SARS-CoV-2 because his lipid envelope can be readily degraded by ozone [14] , [18] . However, robust experimental evidence on the efficacy of this disinfectant under realistic conditions checking also for residual viral viability is still lacking finally limiting the establishment of well-defined decontamination procedures that is a paramount priority.…”
Section: Introductionmentioning
confidence: 99%